Aflatoxin M1 levels in sow milk - PRODANOV-RADULOVIĆ, J.; ŽIVKOV-BALOŠ, M.; JAKŠIĆ, S.; GRGIĆ, Z.; STOJANOV, I.; BOJKOVSKI, J.; TASSIS, P. D. (Journal of the Hellenic Veterinary Medical Society, 2018)
Aflatoxins (AFs) are one of the most known and investigated group of mycotoxins, which can be found as contaminants in different types of food and feed. Animals are exposed to AFs mainly through the consumption of contaminated feed, particularly products of plant origin. Among AFs, aflatoxin M1 (AFM1) is the monohydroxylated derivative of AFB1 formed in the liver and excreted into the milk of lactating animals. This study encompassed the Vojvodina region of Serbia and was aimed at determining the levels of AFM1 excretion in sows’ milk in the first 3‒5 days of lactation, after consumption of naturally contaminated with AFB1 maize. A total of 110 sows’ milk samples from 11 swine farms in the specific region were analyzed by Enzyme Linked Immunosorbent Assay (ELISA). Different levels of AFM1 were detected in the majority (97%) of the examined milk samples. The obtained results showed AFM1 levels ranging from 5 to 165.4 ng/L. The results of this study pose special health concern associated with aflatoxin contamination of swine feed raw materials in this particular part of Serbia. Moreover, such high incidence of AFM1 detection in sows’ milk may suggest the occurrence of long-term low level aflatoxicosis clinical cases.